Total Gluteal Reconstruction with “IGA-based V–Y Myocutaneous Advancement Flap” - Vathulya, Madhubari; Nath, Amborish; Jain, Manish; Seenivasagam, Rajkumar Kottayasamy (Indian Journal of Plastic Surgery, 2019)
Introduction A 44-year-old man was presented with chronic discharging multiple perianal fistula and squamous cell carcinoma of the left buttock.Report The patient was subjected to wide local excision of the entire left gluteal and adjacent sacral regions and reconstruction with extended island inferior gluteal artery based V–Y myocutaneous advancement flap.Result and Conclusion Extended island inferior gluteal based V–Y flap can be a good option for extensive defects involving the gluteal region and the sacrum.
Keywords: gluteal reconstruction; musculocutaneous flap; pedicle flap; post oncological defect